Compliance of Mumbai-based clinical trial sites with the Quality Council of India guidelines and evaluation of the challenges faced by the investigators - Figer, Brinal (Perspect Clin Res, 2021)
PURPOSE: A committee chaired by Dr. Ranjit Roy Chaudhary suggested accreditation of investigators, sites and ethics committees to improve the quality of trial conduct in the country. Prior to accreditation, understanding the challenges faced at the sites by investigators could help define the extent of the problem and identify potential solutions. Hence, we conducted the present study. METHODS: Institutional Ethics Committee approval and written informed consent was obtained prior to enrolment. A checklist and a questionnaire was used to assess compliance to Quality Council of India (QCI) standards and the challenges faced by the sites and investigators respectively. Mumbai based investigators listed in the Clinical Trial Registry of India (CTRI) were enrolled. The responses obtained were analysed descriptively. The responses to each question in the checklist were calculated as a proportion and response to each item in the questionnaire was calculated in frequency and percent frequency. All the analysis was done using Microsoft Excel version 2013. RESULTS: A total of 30 investigators from 69 clinical trial sites agreed to participate. We found that over 80% of the sites complied with standards recommended by the QCI guideline. The most frequently reported issues at the site were lack of space for archival (25%), no System to evaluate adequacy of training (31.81%) and lack of understanding of the technical language of the informed consent form (39.02%). CONCLUSION: There is a need of coordinated effort between all the stakeholders to improve the clinical trial conduct at the site.